Effect of austempering parameters and manganese content on the machinability of austempered ductile iron produced using novel method - Ananda Hegde; Gajanan Anne; Gowrishankar M. C.; Sathyashankara Sharma; Karthik B. M.; Melwyn Rajesh Castelino (Cogent Engineering, 2024)
Austempered ductile iron is an innovative material obtained by subjecting it to an austempering heat treatment. The wide application of this material is because its properties are comparable to those of steel, which has a much lower weight. However, the machinability of this material is always a difficult task owing to its high hardness. This problem becomes more complex when a considerable amount of Mn is added. In this study, a novel two-step austempering heat treatment was performed on spheroidal graphite iron containing different amounts of manganese. Although the novel heat treatment method helps to obtain a superior combination of hardness and impact, its effect on machinability must be determined. This study provides the results of machinability tests carried out on austempered ductile iron with various manganese contents produced using the novel method. Scanning electron microscope images of the microstructures revealed a typical ausferrite structure with no segregation of manganese at the grain boundary. This is evident from the good tool life obtained in the machinability tests. Regression equations are fitted to determine the tool life and surface roughness for machining parameters with a range of values considered in this study. The results obtained have shown that till 1 wt% of manganese alloyed austempered ductile iron can be successfully produced using the novel heat treatment method. This helps to obtain the optimum combination of strength and impact properties.